Application of membrane technology towards the reusability of lake water, mine water, and tube well water - Teow, Yeit Haan; Mohd Syahmi Hafizi Ghani,; Wan Nur Athirah Wan Mohammad Hamdan,; Nurul ‘Adilah Rosnan,; Noorini Izzati Mohamad Mazuki,; Ho, Kah Chun (Penerbit Universiti Kebangsaan Malaysia, 2017)
Severe water shortage caused by El-Nino has caused life-threatening drought conditions globally. This natural disaster has put millions of lives at risk and forcing the people to search for waster. However, the water scarcity problem was not just limited to the countries that were strike by El-Nino. Poor water management and climate change were bringing droughts to Asia and the Pacific. The water scarcity worldwide has recently reached the alarming rate and received the greatest attention among the people. Membrane technology is an innovative technology which has proven to be effective and efficient for water and wastewater treatment. Therefore, membrane technology has high potential to be employed for the treatment of lake water, mine water, and tube well water in increasing the fresh water production for reuse purpose. The objective of this work is to investigate the potential of membrane technology for treating the lake water, mine water, and tube well water. A laboratory bench-scale dead-end test rig was used in this study to evaluate the performance of commercial flat-sheet nanofiltration (NF) - NF270 and reverse osmosis (RO) - BW30 membranes. Both source water and treated water were analysed based on chemical oxygen demand (COD), ammonia nitrogen (NH3-N), colour, total suspended solid (TSS), pH, and temperature. In order to prove the reuse concept of membrane technology, the permeate water quality after the membrane filtration process was compared with National Water Quality Standard (NWQS) of Malaysia. The results from this study shown that the permeate water filtered by NF270 and BW30 membranes were able to meet the NWQS Class III, which was suitable to recycled for livestock drinking and irrigation purposes.